Early-Onset Schizophrenia With Predominantly Negative Symptoms: A Case Study of a Drug-Naive Female Patient Treated With Cariprazine - Molnar, Maria Judit; Jimoh, Idris János; Zeke, Helga; Palásti, Ágnes; Fedor, Marianna (Frontiers in Pharmacology, 2020)
Schizophrenia is a chronic and severe mental disorder characterized by positive, negative, and cognitive symptoms. Negative symptoms are usually present from the prodromal phase; early diagnosis and management of negative symptoms is a major health concern since an insidious onset dominated by negative symptoms is associated with a worse outcome. Antipsychotic medications, which are effective for treating positive symptoms, are generally ineffective for treating negative or cognitive symptoms. We present a 23-year-old woman showing severe symptoms at her first visit to our department. The patient’s parents reported that their daughter had experienced several years of psychosocial decline and putative psychiatric symptoms, but no medical attention had been previously sought; as such, the diagnosis of schizophrenia with predominantly negative symptoms was very much delayed. Early onset of schizophrenia, longer duration of untreated psychosis, and severe negative symptoms, which have limited treatment options, suggested a poor prognosis. We initiated monotherapy with cariprazine, a novel antipsychotic that has recently been proven efficacious in treating schizophrenia with predominantly negative symptoms. This report describes a 52-week cariprazine treatment regimen and follows the patient’s impressive clinical improvement confirmed by PANSS and CGI scores, and psychological tests.